Sexual differences in daily foraging patterns among Great tits Parus major established by radio frequency identification (RFID) tags. Issue 1 (2nd January 2020) - Siekiera, Joachim; Siekiera, Artur; Jankowiak, Łukasz; Tryjanowski, Piotr
Abstract : Providing bird feeders is a very popular interaction between people and birds, and many aspects have been studied in detail. The utilisation of bird feeders in relation to the daylight pattern still needs more research, mostly due to technical problems. This is important for understanding optimal foraging and, in consequence, bird survival. The study was carried out in southern Poland during winter and early spring 2011. A total of 99 Great tits Parus major were tagged of which 50 individuals were recorded at the feeders (in total 2, 771 records). The mean time spent at the feeder by Great tits was 4.3 ± 7.9 sec and was influenced by temperature. During the winter, both sexes showed a bimodal pattern of foraging activity: a first, early morning, peak and a second, evening, peak. In contrast, during early spring we found a significant bimodal pattern only for females with a sharp decrease before dusk. We confirmed that observed foraging patterns could be explained by the risk of starvation and by predator avoidance. Sexual differences in foraging are most probably related to their different activities in late winter/early spring, for example, time-consuming singing by males.